Unified structural adjustment policy in Europe? - Wolfgang Maennig; Helmut Wagner (Intereconomics, 1995)
Low growth and high unemployment have induced the European Union (EU) to outline an economic programme in which long-term effective growth and structural policy measures play a central role. Simultaneously, the German government adopted an “action programme aiming at more growth and employment”, in which the efforts on the EU level play hardly any role. Is international coordination of growth and structural adjustment policy legitimated from an economic point of view or is competition between national policies more efficient?
Keywords: 330; European Union